LAJU PERTUMBUHAN Chaetoceros calcitrans DALAM MEDIA KULTUR EKSTRAK TAUGE PADA SKALA SEMI MASSAL - Mahendra Mahendra (JURNAL PERIKANAN TROPIS, 2015)
The research aims to knowing influence media of bean sprout extract  to growth rate of Chaetocerus calcitrans. This study was conducted on July 2012, at natural feed laboratory (Balai Budidaya Air Payau Situbondo, East Java). This study was using completely randomized design with 4 treatments dan 4 replication, i.e. T0 as control and T1 (MET 2 %), T2 (MET 4 %), and T3 (MET 6 %) as treatment. Growth rate of C. calcitrans. was used as variable test.  Result of study show media of bean sprout extract unsignificant effect to growth rate of C. Calcitrans